Unveiling the Benefits and Challenges of Test-Driven Development in Agile: A Systematic Literature Review - Tampubolon, Sabar Maruba; Raharjo, Teguh (The Indonesian Journal of Computer Science, 2024)
The adoption of Test-Driven Development (TDD) in Agile software development prompts extensive discussion. Advocates highlight its benefits, while skeptics question empirical evidence. This study investigates TDD in Agile settings, examining its merits and challenges. Conducting a systematic literature review, it synthesizes insights from scholarly and industry sources. Results indicate TDD aids development, aligns with Agile practices, and enhances product delivery. Yet, challenges include procedural complexity and skill requirements. Proficiency in Agile practices like refactoring and unit testing is essential. TDD's impact on productivity is moderate and can be counterproductive. This research contributes new perspectives on TDD and Agile development, benefiting academia and informing practitioners for informed decision-making.